The Emerging Role of SGK1 (Serum- and Glucocorticoid-Regulated Kinase 1) in Major Depressive Disorder: Hypothesis and Mechanisms - Dattilo, Vincenzo; Amato, Rosario; Perrotti, Nicola; Gennarelli, Massimo (Frontiers in Genetics, 2020)
Major depressive disorder (MDD) is a heterogeneous psychiatric disease, characterized by persistent low mood, by diminished interests, impaired cognitive and social functions. The multifactorial etiology of MDD is still largely unknown cause the complex genetic and environmental interactions involved. Therefore, no established mechanism can explain all the aspects of the disease. In this light, an extensive research about the pathophysiology of MDD have been carried out. Several pathogenic hypotheses, such as monoamines deficiency and neurobiological alterations in the stress-responsive system, including the hypothalamic–pituitary–adrenal (HPA) axis and the immune system, have been proposed for MDD. Over time, remarkable studies, mainly on preclinical rodent models, linked the serum- and glucocorticoid-regulated kinase 1 (SGK1) to the main features of MDD. SGK1 is a serine/threonine kinase belonging to the AGK Kinase family. SGK1 is ubiquitously expressed, which play a pivotal role in the hormonal regulation of several ion channels, carriers, pumps and transcription factors or regulators. SGK1 expression is modulated by cell stress and hormones, including gluco- and mineralocorticoids. Compelling evidence suggests that increased SGK1 expression or function is related to the pathogenic stress hypothesis of major depression. Therefore, the first part of the present review highlights the putative role of SGK1 as a critical mediator in the dysregulation of the HPA axis, observed under chronic stress conditions and its controversial role in the neuroinflammation as well. The second part depicts the negative regulation exerted by SGK1 in the expression of both the brain-derived neurotrophic factor (BDNF) and the vascular endothelial growth factor (VEGF), resulting in an anti-neurogenic activity. Finally, the review focus on the antidepressant-like effects of anti-oxidative nutraceuticals in several preclinical model of depression, resulting from the restoration of the physiological expression and/or activity of SGK1, which leads to an increase in neurogenesis. In summary, the purpose of this review is a systematic analysis of literature, depicting SGK1 as molecular junction of the complex mechanisms underlying the MDD, in the effort to suggest the kinase as a potential biomarker and strategic target in a modern molecular antidepressant therapy.